Service network design of bike sharing systems with resource-management consideration. - Neumann Saavedra, Bruno Albert (My University, 2018)
Within the last decade, the urban phenomenon bike-sharing has colonised cities' streets on a global scale. Presented as an individual-collective sustainable mobility service, the transportation effects of bike-sharing schemes are said to change urban environments into sustainable cities . Yet, a careful examination first notices that implemented bike-sharing services do not fulfil their sustainability promise. Second, it shows that they are actually the product of often long-established coalitions of interest between the outdoor advertising industry and municipalities, and whose action turns public space into attractive sites of public promotion. Considering in addition that advertisers have seized the techniques of the happening and other perception altering artistic innovations of the 1960s to operate them into their economic management of human attention, this master thesis suggests that the raison d'être of the bike-sharing phenomenon lies in its provision of an aesthetic experience transforming the perception of urban space and life by performing "urban sustainable mobility".
Keywords: Individualverkehr; Fahrradverkehr; Mobilität; Stadtverkehr; Verkehrsinfrastruktur; Stadtraum; Verkehrsplanung; Radverkehrsplanung; Bike-Sharing; Fahrradverleih; Fahrradverleihsystem; Öffentliches Fahrradverleihsystem; Sharing Economy